2020
DOI: 10.3389/fbioe.2020.579751
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Signatures of Synovial Fluid Multipotent Stromal Cells in Advanced Knee Osteoarthritis and Following Knee Joint Distraction

Abstract: Synovial Fluid MSC Gene Expression (weeks 3 and 6). Additionally, early KJD changes (week 3) were marked by significant increases in MSC chondrogenic commitment markers gremlin 1 (GREM1) and growth differentiation factor 5 (GDF5). In combination, our results reveal distinct transcriptomes on joint-resident MSCs from different biomechanical environments and show that 6week joint off-loading leads to transcriptional changes in SF MSCs that may be beneficial for cartilage regeneration. Biomechanical factors shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 97 publications
2
17
0
Order By: Relevance
“… 49 Recently, it was shown that unloading of the joint by KJD resulted in a significant increase in synovial fluid MSC (SF-MSC) colony size and density. 50 Furthermore, after 3 weeks of KJD treatment many transcriptional changes were found in these SF-MSC compared to baseline. These changes included a sustained upregulation of ACAN and a significant increase of the MSC chondrogenic commitment markers gremlin 1, and growth differentiation factor 5 ( GDF5 ), markers associated with cartilage homeostasis and OA, among others.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“… 49 Recently, it was shown that unloading of the joint by KJD resulted in a significant increase in synovial fluid MSC (SF-MSC) colony size and density. 50 Furthermore, after 3 weeks of KJD treatment many transcriptional changes were found in these SF-MSC compared to baseline. These changes included a sustained upregulation of ACAN and a significant increase of the MSC chondrogenic commitment markers gremlin 1, and growth differentiation factor 5 ( GDF5 ), markers associated with cartilage homeostasis and OA, among others.…”
Section: Discussionmentioning
confidence: 92%
“…These changes included a sustained upregulation of aCaN and a significant increase of the MSC chondrogenic commitment markers gremlin 1, and growth differentiation factor 5 (GdF5), markers associated with cartilage homeostasis and OA, among others. [50][51][52] In addition, the joint environment during KJD is changed, favoring attachment of MSC. 21 Another proposed mechanism is the effect of the periarticular bone turnover on the cartilage, as a decrease in subchondral bone sclerosis has been reported in humans and rats after KJD, which was directly associated with the reported clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression was measured using standard TaqMan assays (Thermo Fisher Scientific) and the 48 3 48 integrated fluidic circuit with the recommended reagents (Fluidigm), as previously described. 46 The integrated fluidic circuit was then run on the BioMark real-time polymerase chain reaction system using a GE 48 3 48 Standard Version 1 polymerase chain reaction thermal protocol, and data were analyzed using BioMark Gene Expression Data software and normalized to the housekeeping gene hypoxanthine phosphoribosyltransferase 1.…”
Section: Preparation Of Autologous and Allogenic Pcmentioning
confidence: 99%
“…Their characteristics like self renewably, anti-in ammatory and immunomodulatory effects have made them as a promising option for treatment of diseases [6]. Moreover, MSCs, multipotent stromal cells, can differentiate into multiple lineages of cells including chondrocytes (cartilage) and osteoblasts (bone) whereby limitations of poor intrinsic regeneration of cartilage tissue lesion due to the disability of resident articular chondrocytes to secrete a matrix could be reparated [7]. Derived-MSCs of various sources such as amniotic uid, bone marrow, umbilical cord, adipose tissue, synovial uid, have been evaluated in a lot of experimental studies about different diseases.…”
Section: Introductionmentioning
confidence: 99%